PUEDE LA TECNOLOGÍA DISMINUIR LA DESIGUALDAD? EVIDENCIA EMPÍRICA UTILIZANDO TECNICAS DE DATOS DE PANEL EN 61 PAÍSES DEL MUNDO, DURANTE EL PERÍODO 2000-2015” - Vargas Criollo, Gabriela Estefanía (2020)
Inequality is the central problem of research, its increase and evolution make it a matter of public interest, and in turn marks it as a threat to which we need to find solutions that help to undermine its impact, is outrageous to know nearly half the global population (50%) live on less than $5.5 a day while 1% is rich. Considering the study problem I propose a general aim this is, to evaluate the impact of technology on inequality. Continuing the process we have the methodology I applied panel data, through an ordinary least squares model (OLS) and generalized least squares model (GLS) for 61 countries of worldwide, these were classified according ATLAS (2019), during 20002015. I using control variables to robust the research, such as: education, tax, exportation and urbanization; firstly, the results of OLS model showed that the education has a statistically significant relationship from HMIC, while that the tax is statistically significant for all group, except GLOBAL group; therefore, the GLS results are statistically significant for all group and for all variables, except HMIC group. As a personal contribution I proposed the crowdfunding, which is a means of opportunities for entrepreneurs, their ideas are exposed although a digital platform where various companies visualize these projects and decide to invest, this opportunity could improve the productivity and to generate employment. Keywords: Tecnology. Inequality.